Answer:
First, let's move all terms to one side,
[tex]\sf x^2-8x+6=0[/tex]
When given this form (ax^2+bx+c=0), there will be two solutions at the end.
1) [tex]\sf x=\frac{-b+\sqrt{b^2-4ab} }{2b}[/tex]
2) [tex]\sf x=\frac{-b-\sqrt{b^2-4ab} }{2b}[/tex]
where, a=1, b=-8, c=6
[tex]\sf x=\frac{8+\sqrt{(-8)^2-4\times6} }{2} ,\frac{8-\sqrt{(-8)^2-4\times6} }{2}[/tex]
Simplify,
[tex]\sf x=\frac{8+2\sqrt{10} }{2} ,\frac{8-2\sqrt{10} }{2}[/tex]
Simplify,
[tex]\sf x=4+\sqrt{10}, 4-\sqrt{10}[/tex]
Hope it helps!